2003
DOI: 10.1080/10647440400009896
|View full text |Cite
|
Sign up to set email alerts
|

HPV Prevalence and Concordance in the Cervix and Oral Cavity of Pregnant Women

Abstract: Objectives: This investigation examined human papillomavirus (HPV) in pregnant women in order to characterize viral prevalence, types and concordance between infection in the cervix and in the oral cavity. Methods: A total of 577 pregnant women seeking routine obstetric care were evaluated for HPV infection in their cervix during gestation and immediately before delivery, and in the oral cavity during gestation. Male partners present during the gestational clinic visit also provided a specimen from their oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
67
3
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 40 publications
(45 reference statements)
8
67
3
16
Order By: Relevance
“…One patient was found type 16/30, the others were untyped. 32 We have found that 2.2% of the patients were positive for HPV 18 in our study where Smith et al 29 found that 2.6% of the patients were positive in favor of HPV 18. The association between HSV-2 and HPV 18 was found in one of the pregnant women.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…One patient was found type 16/30, the others were untyped. 32 We have found that 2.2% of the patients were positive for HPV 18 in our study where Smith et al 29 found that 2.6% of the patients were positive in favor of HPV 18. The association between HSV-2 and HPV 18 was found in one of the pregnant women.…”
Section: Discussionmentioning
confidence: 59%
“…28 Epidemiological studies revealed different results in pregnant women. Smith et al, 29 Gajewski et al 30 and Takakuwa et al 31 have found out 29%, 26% and 12.5% of HPV positivity respectively in pregnant women taking routine obstetric care. In a study performed in our country, HPV DNA was found as 9.5% by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Otro aspecto a considerar en cuanto a las diferencias en la detección de VPH en boca y cérvix es la variación en la susceptibilidad a la infección por VPH y/o el tropismo viral, así como la capacidad de resolver la infección en ambas regiones, la cual puede ocurrir de manera independiente o en intervalos diferentes 22 . En este estudio el tipo viral más frecuente fue VPH tipo 6, encontrado en un 86,2% de las muestras bucales y en un 65,9% de las muestras cervicales, tanto solo como en combinación con otros tipos de alto (16,18,33) y/o de bajo (11) riesgo oncogénico; el tipo de alto riesgo más frecuente fue el 16.…”
Section: Discussionunclassified
“…4,5 In this case report, a patient presented asymptomatic cervical lesions that were suggestive of HPV infection, which were identified through white staining after acetic acid application, and were diagnosed by means of cytopathological examination as low-grade intraepithelial lesions. Identification of high-risk HPV56 in the cervical lesions showed the importance of using molecular techniques for identifying the subtype of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some studies have attempted to find evidence of an association and/or relationship between HPV infection in the mouth and genitalia of pregnant women. 4,12 The studies that have reported HPV infection in the mouth and genitalia in pregnant women are listed in Table 1. These studies observed presence of HPV at both of these anatomical sites.…”
Section: Discussionmentioning
confidence: 99%